The Time of Enlightenment Constructing the Future in France, 1750 to Year One - Nelson, William Max (University of Toronto Press, 2020)
A new idea of the future emerged in eighteenth-century France. With the development of modern biological, economic, and social engineering, the future transformed from being predetermined and beyond significant human intervention into something that could be dramatically affected through actions in the present. The Time of Enlightenment argues that specific mechanisms for constructing the future first arose through the development of practices and instruments aimed at countering degeneration. In their attempts to regenerate a healthy natural state, Enlightenment philosophes created the means to exceed previously recognized limits and build a future that was not merely a recuperation of the past, but fundamentally different from it. A theoretically inflected work combining intellectual history and the history of science, this book will appeal to anyone interested in European history and the history of science, as well as the history of France, the Enlightenment, and the French Revolution.